Integration of Video-Based Learning Media in Animal Reproduction Lessons to Elevate Academic Achievement in Fourth Graders at Tunas Bakti Elementary School - Yuliana, Leni; Desiningrum, Noviana; Yudianto, Firman (JURNAL PENDIDIKAN DAN PENGEMBANGAN MANUSIA, 2023)
Problems in the learning process experienced in some elementary schools are less effective and efficient learning processes carried out by teachers so that student learning outcomes tend to be low. This study aims to Improve Student Learning Outcomes Using Learning Video Media in Grade 4 Student Animal Reproduction Materials SD Tunas Bakti Surabaya. This study uses classroom action research carried out in 2 cycles, each cycle consisting of 4 stages of planning, implementation, observation, and reflection. The results showed that science learning using video learning media can improve student learning outcomes compared to before classroom action research was conducted.